Multiple impressions : contemporary Chinese woodblock prints - Tang, Xiaobing, 1964-; Hui, Shang; Farrer, Anne.; University of Michigan. Museum of Art (Ann Arbor, Mich. : University of Michigan Museum of Art ; Seattle, Wash. : Distributed by University of Washington Press, 2011)
Multiple Impressions examines works by 40 leading printmakers from contemporary China, highlighting the extraordinary innovations, in both technique and conception, which have transformed this long-established art form in recent years. It includes works by such artists as Xu Bing, Kang Ning, Song Yuanwen, Chen Qi, He Kun, and Fang Limin, as well as many other accomplished printmakers.
Essays by noted scholars place contemporary printmaking in its complex art historical and cultural contexts, discuss the relationship between printmaking and contemporary art, and interpret new work by the internationally prominent artist Xu Bing. The book explores three key themes in printmaking today: "Landscapes Old and New" illustrates the variety of techniques and visual idioms contemporary printmakers draw on to create expressive and fantastic landscapes; "Fellow Citizens" turns to the human figure; and "Layered Abstractions" focuses on works that showcase the distinct visual effects and pictorial language that underscore the process of making a print--Publisher description.
Foreword -- Introduction: Continual experimentation in modern Chinese printmaking / Xiaobing Tang -- Chinese printmaking in the twenty-first century : new horizons and energies / Shang Hui -- Xu Bing's Mustard seed garden landscape scroll / Anne Farrer -- Landscapes old and new -- Fellow beings -- Layered abstractions.
Catalogue accompanying exhibition, University of Michigan Museum of Art, July 16-Oct. 23, 2011.
Includes bibliographical references (page 143).
Keywords: Wood-engraving, Chinese -- 21st century -- Exhibitions